Telipogon pillaropatatensis (Oncidiinae) : a new species from the East-Central Andes of Ecuador - Iturralde, Gabriel Alfredo; Monteros, Marco F.; Jiménez, Marco M.; Martel, Carlos; Baquero R., Luis E. (2023)
A new species, Telipogon pillaropatatensis, is described from the highlands of east-central Ecuador. It is morphologically similar to T. octavioi but differs by having a corolla with longitudinal thick vein lines without reticulations and a column with three dense bundles of equally sized setae. Also, our phylogenetic analyses suggest that they are not closely related. Interestingly, among the analyzed taxa, T. pillaropatatensis appears to have a closer phylogenetic relationship with the highly distinct T. pulcher and T. hausmannianus than with the morphologically similar T. octavioi. The new species has been found in a relatively small area, covering just a few square kilometers in east-central Ecuador. Additionally, we documented remarkable variation in the coloration and size of the corolla. Information regarding the species' habitat, ecology, phylogenetic relationships, and conservation status is also provided.
Se describe una nueva especie, Telipogon pillaropatatensis, de las tierras altas del centro-este de Ecuador. Morfológicamente es similar a T. octavioi, pero se diferencia por tener una corola con líneas longitudinales gruesas sin reticulaciones y una columna con tres densos penachos de setas de igual tamaño. Además, nuestros análisis filogenéticos sugieren que ambas especies no están estrechamente relacionadas. Curiosamente, entre los taxones analizados, T. pillaropatatensis parece tener una relación filogenética más cercana con las muy distintas T. pulcher y T. hausmannianus que con la morfológicamente similar T. octavioi. La nueva especie ha sido encontrada en un área relativamente pequeña, abarcando solo unos pocos kilómetros cuadrados en el centro-este de Ecuador. Además, documentamos una notable variación en la coloración y el tamaño de la corola. También se proporciona información sobre el hábitat, la ecología, las relaciones filogenéticas y el estado de conservación de la especie.
Keywords: ORQUIDEAS -- ECUADOR; ORQUÍDEAS -- FILOGENIA; ORQUIDEAS -- INVESTIGACIONES -- ECUADOR